Enterprise Information Systems 9th International Conference, ICEIS 2007, Funchal, Madeira, June 12-16, 2007, Revised Selected Papers - Filipe, Joaquim.; Cordeiro, Jos.̌; Cardoso, Jorge. (Lecture Notes in Business Information Processing, 2009)
This books contains the best papers of the 9th International Conference on Enterprise Information Systems, ICEIS 2007, held in Funchal, Madeira, Portugal, in June 2007. The 6 invited papers are presented together with 23 papers which were carefully reviewed and selected from 72 full papers accepted for presentation at the conference itself (out of 644 submissions). The topics covered are: databases and information systems integration; artificial intelligence and decision support systems; information systems analysis and specification; software agents and internet computing; and human-computer interaction.